Fluorescence relaxation kinetics of poly(methylphenylsilane) film and nanocomposites - Ostapenko, N. (Nanoscale Res Lett, 2016)
A comparative study of fluorescence relaxation kinetics of σ-conjugated poly(methylphenylsilane) (PMPS) polymer film and nanocomposites has been performed by ultrafast time-gated fluorescence measurements at various temperatures. Investigations have revealed a fine structure of excitonic σ-σ* band. We attribute this structure to emission from two spatially independent states with different ordering of the polymer chain segments, type gauche and trans conformations. In contrary to a more ordered polymer poly(di-n-hexylsilane), no clear thermochromic transition has been detected in PMPS film; however, the trans band intensity increases with temperature and with excitation wavelength, but it is absent when polymer is incorporated into nanopores of small diameter.